2014
DOI: 10.3892/or.2014.3126
|View full text |Cite
|
Sign up to set email alerts
|

Altholactone induces reactive oxygen species-mediated apoptosis in bladder cancer T24 cells through mitochondrial dysfunction, MAPK-p38 activation and Akt suppression

Abstract: Human bladder cancer is an aggressive tumor which frequently resists chemotherapy. Therefore, the search for new therapeutic agents is of great importance. Altholactone, isolated from Goniothalamus sp., has been reported to inhibit the growth of various types of cancer cells. However, no prior research has been conducted to demonstrate the antiproliferative potential of altholactone on bladder cancer. In the present study, we characterized the effect of altholactone on cell growth and apoptosis in bladder canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
20
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
(41 reference statements)
4
20
0
Order By: Relevance
“…Several reports have demonstrated that HSP27 can form multicomponent complexes with Akt, and P38, and this complex has been shown to be involved in controlling HSP27 phosphorylation and stress-induced apoptosis [ 17 , 27 , 28 ]. As reported previously, activation of P38 was accompanied by Akt suppression in the apoptotic process in some types of cancer cells [ 29 , 30 ]. Conversely, there also has a good evidence suggesting a link from MEKK4 and P38, via HSP27, to Akt activation, which is essential for the regulation of cell fate in response to apoptotic stress in human prostate cancer cells [ 31 ].…”
Section: Discussionsupporting
confidence: 70%
“…Several reports have demonstrated that HSP27 can form multicomponent complexes with Akt, and P38, and this complex has been shown to be involved in controlling HSP27 phosphorylation and stress-induced apoptosis [ 17 , 27 , 28 ]. As reported previously, activation of P38 was accompanied by Akt suppression in the apoptotic process in some types of cancer cells [ 29 , 30 ]. Conversely, there also has a good evidence suggesting a link from MEKK4 and P38, via HSP27, to Akt activation, which is essential for the regulation of cell fate in response to apoptotic stress in human prostate cancer cells [ 31 ].…”
Section: Discussionsupporting
confidence: 70%
“…Importantly, aberrant regulation of MAPK could contribute to cancer and other human diseases, including bladder cancer [6, 7]. Many studies have suggested that intracellular or extracellular calcium disorders might induce abnormal activation or deactivation of MAPK cascades [8, 9] and consequently initiate cancer development [10].…”
Section: Introductionmentioning
confidence: 99%
“…1 B), suggesting that the effect of GPE on apoptosis was specific to cancer cells (8 , 11 , 22 , 23) . Considering the critical role of Akt pathway in the progression of bladder cancer (14 , 15 , 26) , with no corresponding cytotoxic effect on normal cells, our findings suggest that GPE can be a promising therapeutic candidate for the development of an anti-cancer drug for bladder cancer.…”
Section: Discussionmentioning
confidence: 86%
“…Akt is the typical survival factor in various cancer cells, including bladder cancer (13 - 15) , and Akt suppression was critical for exhibiting the anti-tumor effect of various bioactive peptides (14 , 16) . In addition, we had previously shown GPE induced cervical cancer cell death by inhibiting the Akt pathway (11) .…”
Section: Resultsmentioning
confidence: 99%